The Effect of Perceived Organizational Support on Employee Engagement - Claudianty, Grandita Satira; Suhariadi, Fendy (FENOMENA, 2020)
This study aims to determine the direct effects of perceived organizational support on employee engagement. The sample used was 111 of PT X employees with more than one year work. The sampling technique used in this study was a purposive sampling. This study uses a Utretch Work Engagement Scale developed by Schaufeli and Bakker (2004) with reliability of 0,888 and Survey of Perceived Organizational Support developed by Rhoades dan Eisenberger (2002) with reliability of 0,947. Data analysis uses partial least square method with the help of Smart-PLS 3.0. software. The results show that there is a positive and significant direct effect of perceived organizational support on employee engagement.